What affects bank market power in the euro area? A country-level structural model approach. (October 2021) - Coccorese, Paolo; Girardone, Claudia; Shaffer, Sherrill
Highlights: We examine bank market power in 13 Euro area banking sectors through a structural model. The two-equation model is estimated using aggregate data for the years 2007 to 2019. Banks' mark-up is parameterized as a measure of banks' conduct depending on selected factors. EU banks appear to enjoy substantial market power, decreasing and converging over time. More competition is associated with higher bank density, efficiency and stability. Abstract: In this study we explore market power in 13 euro area banking sectors for the years 2007 to 2019 by means of a structural model framework with demand and supply equations, where the mark-up of price over marginal cost is parameterized as a measure of banks' conduct that depends on selected factors. Our evidence indicates that EU banks enjoy a significant degree of market power, which shows a decreasing trend over time and some difference across countries. More competition is associated with higher bank density, lower bank capitalization, more efficient and stable banking systems, better macroeconomic conditions, and the establishment of the SSM. Finally, a clear convergence pattern emerges in the behaviour of EU banks.